Use of the Skin Cancer Quality of Life Impact Tool (SCQOLIT) – a feasibility study in non‐melanoma skin cancer. (16th September 2019) - Wali, G.N.; Gibbons, E.; Kelly, L.; Reed, J.R.; Matin, R.N.
Abstract: Background: Incidence of non‐melanoma skin cancers (NMSCs) is increasing and can significantly impact on quality of life (QOL), yet there are few studies evaluating patient‐reported outcome measures (PROMs) in NMSC populations. We undertook a prospective feasibility study to evaluate a skin cancer‐specific PROM, the Skin Cancer Quality of Life Impact Tool (SCQOLIT), in patients with a new diagnosis of NMSC. Objectives: (i) To establish acceptability of SCQOLIT in dermatology clinics, (ii) a descriptive analysis of SCQOLIT scores in NMSC. Methods: Patients with histologically confirmed NMSC completed SCQOLIT, EQ‐5D and a transition item. Questionnaires were completed at baseline and 3 months for group 1 ('low‐risk' NMSC) and group 2 ('high‐risk' NMSC) with additional questionnaires at 6–9 months for group 2. Patients participated in structured interviews. Clinician experience was captured through staff evaluation forms and a focus group. Acceptability and psychometric properties of SCQOLIT were assessed. Results: Overall, 318 patients consented to participate. Mean SCQOLIT score at baseline was 5.33, with 2.6% of patients scoring ≥20. No ceiling effects were observed, whilst 13.9% scored 0. Validity was demonstrated against EQ‐5D. Cronbach's alpha 0.84 demonstrated internal consistency. Thirteen patients were interviewed and thought SCQOLIT was comprehensive, captured impact on health‐related QOL and helped express their needs to clinicians. Most clinicians found SCQOLIT 'very useful' or 'useful to some extent' in facilitating discussions. Conclusions: This feasibility study demonstrates that SCQOLIT is acceptable to patients and staff in dermatology skin cancer clinics. The psychometric properties of SCQOLIT confirm its utility in NMSC populations.